Comparison of distributed technologies for defining a distributable and interoperable ETL framework - Abdullah, Mohd Syazwan; Awad, Mohammed M I; Saleh, Abdul Razak; Mat Ali, Abdul Bashah; Ahmad, Azizah (2012)
Extraction, Transformation and Loading (ETL) are major functionalities in data warehousing. Lack of component distribution and interoperability are the main problems in the ETL area, because ETL components are tightly-coupled in the traditional ETL framework. This paper explores and discusses five popular distributed technologies for the purpose of highlighting the best technology that is capable of overcoming the distribution and interoperability gaps of the traditional ETL framework. Based on the comparison of distributed technologies discussed in this paper, several benefits can be obtained when SOA is used in redefining the ETL framework such as: distribution, interoperability, reusability, portability, and compatibility with legacy systems. These advantages and other SOA specifications are discussed in this paper.